Village Head Election Contention and Governance Disruption: A Case Study of Benteng, East Luwu - Yusriah Amaliah; Andi M. Ferian Maha Putra Parial (Journal of Contemporary Local Politics, 2026)
This article examines how electoral contention in village head elections disrupts day-to-day village governance. Framed around the question of how political competition affects administrative stability at the village level, the study conceptualizes elections as a governance stress test. Using a qualitative single-case study of Benteng Village in East Luwu, Indonesia, the research draws on semi-structured interviews, direct observation, and analysis of village budget documents from 2019-2021.The findings reveal three interconnected mechanisms of governance disruption. First, intense electoral contestation undermined organizational cohesion within the village apparatus through loyalty pressures and staff instability. Second, post-election governance was marked by elite-dominated deliberation, weakening inclusive participation, particularly among women and youth. Third, electoral dynamics reshaped budget priorities and exposed integrity vulnerabilities, contributing to administrative delays and declining public trust. The article contributes theoretically by linking electoral contention to governance performance through a mechanism as based framework, extending debates on clientelism, participatory governance, and collaborative capacity. Practically, it highlights the need for neutral leadership transitions, strengthened deliberative safeguards, and proactive transparency to protect village governance from electoral shocks.